Balanced approach for tendering practice at the pre-contract stage: the UK practitioner’s perspective - Whang, Seoung-Wook; Donyavi, Sohrab; Flanagan, Roger; Kim, Sangyong (Journal of Civil Engineering and Management, 2022)
Tender documents often lack clarity and are incomplete, making it difficult for contractors to appropriately price projects. A general view is that the quality of tender documents has declined, which has affected the bidding strategies of contractors. However, the academic literature has focused mainly upon the views of contractors. To obtain a more balanced view of tendering practices, in-depth interviews were conducted with 10 practitioners (client, consultant, and contractor) who are involved in a common project at the same time in the UK construction industry. The contractor was satisfied that the quality of tender documents had been consistent. By contrast, both the client and the consultant agreed that the quality of tender documents is an ongoing issue. During the study it was revealed that tendering practice is influenced by the relationship between stakeholders or the unbalanced access to information rather than the accuracy and analysis of tender documentations. Tendering practices and proposed efficient ways of improving the bidding environment were examined. Using the awareness of other project stakeholder’s perspectives, this study can help the contractor to establish suitable tendering practices, and to mitigate tender risk at the bidding stage, which could effectively be implemented in the UK construction industry.